Zinc acrylate resin, tin-free self-polishing antifouling paint containing zinc acrylate resin and preparation method of zinc acrylate resin

By combining acrylic zinc resin with modified silane and other materials, Wuxi self-polishing antifouling coating is prepared, which solves the problems of short antifouling performance, high environmental harm and complex preparation process of existing coatings, and achieves efficient and environmentally friendly antifouling. effect and good self-polishing performance.

CN119331155APending Publication Date: 2025-01-21GUANGDONG WEIQI NEW MATERIAL TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411882454.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-19
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

现有无锡自抛光防污涂料存在防污性能短、铜作为重金属元素对环境有害、制备工艺复杂且能耗高的问题。

Method used

Using acrylic zinc resin as the main component, an acrylic acid-alachlor complex is prepared through the reaction of acrylic acid and alachlor, and combined with materials such as modified silane and zinc oxide to prepare a high antifouling agent release rate and good self-efficiency. Wuxi self-polishing antifouling coating with polishing effect.

Benefits of technology

The coating has good mechanical properties, flexibility, oxidation resistance and aging resistance, significant antifouling effect, stable release of fungicides, excellent self-polishing effect, little harm to the environment, and extended antifouling period.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention provides zinc acrylate resin, a tin-free self-polishing antifouling coating containing the zinc acrylate resin and a preparation method of the zinc acrylate resin, and belongs to the technical field of coatings. The preparation method comprises the following steps: mixing the zinc acrylate resin, the rosin, the antifouling agent, the iron oxide red, the talcum powder, the auxiliary agent and the xylene according to the formula ratio, stirring for 2-4 hours at the speed of 1000-1200 r / min, and grinding until the fineness is 1t; the thickness is 100 microns, so that the tin-free self-polishing antifouling paint is prepared. The tin-free self-polishing antifouling paint prepared by the invention has good mechanical properties, flexibility, oxidation resistance, aging resistance, antifouling effect, stable bactericide release and excellent self-polishing effect, has excellent antifouling effect in the advancing process of a ship and in still water, has small harm to the environment, has stable antifouling agent release rate, and can be widely applied to the fields of ships, ships and the like. And the antifouling period is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of coatings, and in particular to a zinc acrylate resin, a Wuxi self-polishing antifouling coating containing the resin, and a preparation method thereof. Background Art

[0002] As we all know, marine fouling organisms adhere to and grow on the underwater hull of ships, which not only increases the mass of the hull itself, but also significantly increases the roughness of the bottom surface of the ship, increases the friction resistance of the ship during navigation, and thus consumes more ship fuel, causing serious harm to the navigation of the ship. In order to reduce this harm, people have invented and used various types of antifouling coatings, such as traditional, release, ablative, etc. Although these antifouling paints are effective, they still have various disadvantages that cannot be ignored: short antifouling time; easy to form a "sandwich" shell system, etc. The antifouling paint bactericide is basically based on cuprous oxide. In the 1950s, people found that adding tributyltin (TBT) to antifouling paint can effectively inhibit the growth of barnacles and algae, reduce the navigation resistance caused by the attachment of marine organisms, reduce fuel costs, and effectively extend the maintenance cycle of ships, so organotin antifouling paint has been widely used. However, people gradually discovered that oysters containing toxic tributyltin gradually appeared in coastal waters and species mutations caused by this phenomenon, confirming that the use of tributyltin fungicides in antifouling paints will cause serious ecological and economic harm to marine life, and human health may also be harmed by consuming contaminated seafood. Therefore, in January 2008, the use of antifouling paints containing organic tin biocidal materials was banned in global waters, giving rise to a series of substitutes. At present, the mainstream antifouling paint in the international market is Wuxi self-polishing antifouling paint with zinc acrylate / copper resin as film-forming material and cuprous oxide as the main antifouling agent.

[0003] Ordinary Wuxi self-polishing antifouling coatings have the following defects: (1) If the ship's speed is too low or the mooring time is too long, the antifouling performance will be reduced or even ineffective; (2) At a high polishing rate, the thickness of the release layer formed on the coating surface increases with the polishing time, affecting the effective seepage of the subsequent antifouling agent; (3) Copper, as a heavy metal element, is inherently toxic and cannot be biodegraded. Large amounts of copper accumulated in the ocean or harbor will cause the death of seaweed, reduce the breathing rate of mussels and other shellfish, damage their growth process, and seriously disrupt the ecological balance.

[0004] Chinese patent document CN106675294A discloses "copper-free environmentally friendly self-polishing marine antifouling coating". The marine antifouling coating of the invention has good self-polishing performance, does not contain any copper antifouling agent, can greatly reduce copper emissions, save a lot of heavy metal resources, has no pollution to the marine environment, and is of great significance in protecting the marine environment. However, the raw material preparation process of the invention is complicated, the energy consumption is high, and it is not conducive to large-scale industrial production. Summary of the invention

[0005] The purpose of the present invention is to provide a zinc acrylate resin, a Wuxi self-polishing antifouling paint containing the resin and a preparation method thereof, which has good mechanical properties, flexibility, oxidation resistance and aging resistance, good antifouling effect, stable bactericide release, excellent self-polishing effect, excellent antifouling effect when the ship is moving and in still water, little harm to the environment, high antifouling agent release rate, and prolonged antifouling period.

[0006] The technical solution of the present invention is achieved in this way: The present invention provides a method for preparing zinc acrylate resin, comprising the following steps: S1. Reaction of acrylic acid and alachlor: acrylic acid and alachlor were mixed and added to acetonitrile, a base was added, the reaction was stirred, filtered, washed, and dried to obtain an acrylic acid-alachlor complex; S2. Preparation of acrylic prepolymer: 2-butyloxyethyl acrylate, acrylic acid, butyl acrylate, perfluorohexylethyl methacrylate, acrylic acid-alachlor complex were mixed, an initiator, n-dodecyl mercaptan and a solvent were added, and the reaction was heated and stirred to obtain an acrylic prepolymer; S3. Preparation of modified silane: adding nano-silica to ethanol, adding composite silane, heating and stirring the reaction, removing the solvent under reduced pressure to obtain modified silane; S4. Preparation of acrylic acid / silane prepolymer: adding modified silane to acrylic acid prepolymer, adding an initiator, heating and stirring the reaction to obtain acrylic acid / silane prepolymer; S5. Preparation of zinc acrylate resin: acrylic acid / silane prepolymer, benzoic acid and zinc oxide are uniformly mixed, heated and stirred to react, propylene glycol monomethyl ether is added and stirred to mix, and the reaction is terminated to obtain zinc acrylate resin.

[0007] As a further improvement of the present invention, the molar ratio of acrylic acid, alachlor and base in step S1 is 1:0.9-1:3-5, the base is selected from triethylamine, NaOH or KOH, the stirring reaction temperature is 60-70°C, and the time is 3-5h.

[0008] As a further improvement of the present invention, the mass ratio of 2-propenoic acid-2-butoxyethyl ester, acrylic acid, butyl acrylate, perfluorohexylethyl methacrylate, acrylic acid-alachlor complex, initiator, n-dodecyl mercaptan, and solvent in step S2 is 2-4:3-5:1-2:0.5-1.5:1-2:0.05-0.1:0.05-1:10-15, the temperature of the heating and stirring reaction is 110-120°C, and the time is 3-5h. The initiator is selected from at least one of azobisisobutyronitrile, dimethyl azobisisobutyrate, azobisisovaleronitrile, and azobisisoheptonitrile, and the solvent is toluene or xylene.

[0009] As a further improvement of the present invention, the average particle size of the nano-silica in step S3 is 80-120nm, the mass ratio of the nano-silica to the composite silane is 1-2:7-10, the composite silane includes a mixture of KH570, KH550, and KH580 in a mass ratio of 3-4:2-3:1-2, the temperature of the heating and stirring reaction is 40-50°C, and the time is 1-2h.

[0010] As a further improvement of the present invention, the mass ratio of the modified silane, acrylic prepolymer and initiator in step S4 is 3-5:10:0.01-0.02, the initiator is selected from at least one of azobisisobutyronitrile, dimethyl azobisisobutyrate, azobisisovaleronitrile and azobisisoheptylonitrile, the temperature of the heating and stirring reaction is 110-120° C., and the time is 2-3 hours.

[0011] As a further improvement of the present invention, the mass ratio of acrylic acid / silane prepolymer, benzoic acid, zinc oxide and propylene glycol monomethyl ether in step S5 is 100:12-13:8-8.5:10-12, and the temperature of the heating and stirring reaction is 110-120° C. and the time is 3-5 hours.

[0012] The present invention further protects a zinc acrylate resin prepared by the above preparation method.

[0013] The present invention further protects a Wuxi self-polishing antifouling paint containing the above zinc acrylate resin, which comprises 30-40 parts of the above zinc acrylate resin, 5-10 parts of rosin, 35-45 parts of antifouling agent, 5-10 parts of iron red, 5-10 parts of talcum powder, 0.5-1 parts of auxiliary agent and 10-15 parts of xylene.

[0014] As a further improvement of the present invention, the antifouling agent is at least one of cuprous oxide, zinc dimethyldithiocarbamate, copper pyrithione, and 4,5-dichloro-2-octyl-4-isothiazoline-3-one, and the auxiliary agent is at least one of a wetting agent, a dispersant, an anti-settling agent, a leveling agent, and a defoaming agent.

[0015] The present invention further protects a method for preparing the above-mentioned Wuxi self-polishing antifouling coating, comprising the following steps: Zinc acrylate resin, rosin, antifouling agent, iron red, talcum powder, additives and xylene are mixed according to the formula, stirred at 1000-1200r / min for 2-4h, and ground to a fineness of less than 100μm to prepare Wuxi self-polishing antifouling coating.

[0016] The present invention has the following beneficial effects: The resin used in the traditional dissolving antifouling coating is soluble rosin and its derivatives, which have poor mechanical properties, high abrasion rate and short service life. The Wuxi self-polishing antifouling coating prepared by the present invention aims at these shortcomings, and adds acrylate zinc resin with high mechanical strength to the rosin resin base material to enhance the oxidation resistance and aging resistance of the coating, and control the dissolution rate of the rosin resin. It also has a higher antifouling agent release rate, improves the antifouling effect when the ship is stationary, and prolongs the antifouling period.

[0017] The prepared zinc acrylate resin releases low-toxic zinc oxide, organic acid zinc and other biocidal aids through the hydrolysis of organic acid zinc, keeps the coating smooth and has an antifouling effect. When the coating is used, zinc ions are dissolved in water as an antifouling agent after hydrolysis. The hydrophilic carboxyl groups are left in the resin, so that the polyacrylic acid resin swells in water until it dissolves. It is washed away by water flow to form a smooth surface, achieving a self-polishing effect. At the same time, the wrapped antifouling agent is released to play an antifouling effect.

[0018] The present invention prepares an acrylic acid-alachlor compound by reacting acrylic acid with alachlor, which has obvious biological inhibition on the attachment of barnacles and seaweeds, and thus has good antifouling performance.

[0019] Ordinary zinc acrylate resin itself does not have antifouling properties. The present invention introduces hydrophobic and hydrophilic monomers. The hydrophobic fluorine-containing monomer makes the resin itself have antifouling properties. At the same time, the hydrophilic monomer makes the resin swell and dissolve in water, thereby playing a self-polishing role, thereby improving the antifouling effect when the ship is stationary.

[0020] In addition, the prepared zinc acrylate resin of the present invention is further added with modified silane, with nano silicon dioxide as the cross-linking core, so as to form a network structure, the composite silane includes silane KH570 with double bonds, silane KH550 with amino groups and silane KH580 with mercapto groups, which can form a complex cross-linking network structure by forming hydrogen bonds, and at the same time, the double bonds can also copolymerize with the acrylic resin, so that the prepared acrylic acid / silane prepolymer forms a network structure, in the weak alkaline environment of seawater, the carboxylic acid group of the resin begins to hydrolyze, and at the same time, the zinc ions are exchanged, gradually converted into a hydrophilic polymer and combined with water molecules to absorb water and swell, the coating surface gradually converts into a polymer with stronger hydrophilicity and absorbs a certain amount of water, with the further penetration of seawater, the copolymer of the inner layer also gradually begins to hydrolyze, and at the same time, due to the cross-linking effect between the copolymers, a thin hydrogel layer is formed on the surface, the introduction of the organic silicone resin promotes the generation of a semi-interpenetrating polymer network, and its binding effect inhibits the peeling of the hydrogel layer, thereby delaying the swelling rate curve, thereby extending the antifouling effect. At the same time, nano-silicon dioxide also improves the flexibility and impact resistance of the coating. The Wuxi self-polishing antifouling paint prepared by the invention has good mechanical properties, flexibility, oxidation resistance and aging resistance, good antifouling effect, stable bactericide release, excellent self-polishing effect, excellent antifouling effect when the ship is moving and in still water, little harm to the environment, high antifouling agent release rate, and prolonged antifouling period. DETAILED DESCRIPTION

[0021] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0022] Nano-silicon dioxide, with an average particle size of 100 nm, was purchased from Beijing Zhongke Keyou Nanotechnology Co., Ltd.

[0023] Example 1 This embodiment provides a method for preparing zinc acrylate resin, comprising the following steps: S1. Reaction of acrylic acid and alachlor: 0.1 mol of acrylic acid and 0.09 mol of alachlor were mixed and added to 500 mL of acetonitrile, and 0.3 mol of triethylamine was added. The mixture was stirred at 60° C. for 3 h, filtered, washed, and dried to obtain an acrylic acid-alachlor complex. S2. Preparation of acrylic acid prepolymer: 2 g of 2-butyloxyethyl 2-acrylate, 3 g of acrylic acid, 1 g of butyl acrylate, 0.5 g of perfluorohexylethyl methacrylate, and 1 g of acrylic acid-alachlor complex were mixed, 0.05 g of azobisisobutyronitrile, 0.05 g of n-dodecyl mercaptan, and 10 g of xylene were added, and the mixture was heated to 110° C. and stirred for reaction for 3 h to obtain an acrylic acid prepolymer; S3. Preparation of modified silane: 1 g of nano-silica was added to 200 mL of ethanol, 7 g of composite silane was added, heated to 40 ° C, stirred for 1 h, and the solvent was removed under reduced pressure to obtain modified silane; The composite silane includes a mixture of KH570, KH550, and KH580 in a mass ratio of 3:2:1; S4. Preparation of acrylic acid / silane prepolymer: 30 g of modified silane was added to 100 g of acrylic acid prepolymer, 0.1 g of azobisisobutyronitrile was added, heated to 110 ° C, stirred for 2 h, and an acrylic acid / silane prepolymer was obtained; S5. Preparation of zinc acrylate resin: 100 g of acrylic acid / silane prepolymer, 12 g of benzoic acid and 8 g of zinc oxide were stirred and mixed for 10 min, heated to 110° C., stirred and reacted for 3 h, 10 g of propylene glycol monomethyl ether was added and stirred and mixed for 0.5 h, and the reaction was terminated to obtain zinc acrylate resin.

[0024] Example 2 This embodiment provides a method for preparing zinc acrylate resin, comprising the following steps: S1. Reaction of acrylic acid and alachlor: 0.1 mol of acrylic acid and 0.1 mol of alachlor were mixed and added to 500 mL of acetonitrile, and 0.5 mol of triethylamine was added. The mixture was stirred at 70° C. for 5 h, filtered, washed, and dried to obtain an acrylic acid-alachlor complex. S2. Preparation of acrylic acid prepolymer: 4 g of 2-butyloxyethyl 2-acrylate, 5 g of acrylic acid, 2 g of butyl acrylate, 1.5 g of perfluorohexylethyl methacrylate, and 2 g of acrylic acid-alachlor complex were mixed, 1 g of azobisisobutyronitrile, 1 g of n-dodecyl mercaptan, and 15 g of xylene were added, heated to 120° C., stirred and reacted for 5 h, to obtain an acrylic acid prepolymer; S3. Preparation of modified silane: 2 g of nano-silica was added to 200 mL of ethanol, 10 g of composite silane was added, heated to 50 ° C, stirred for 2 h, and the solvent was removed under reduced pressure to obtain modified silane; The composite silane includes a mixture of KH570, KH550, and KH580 in a mass ratio of 4:3:2; S4. Preparation of acrylic acid / silane prepolymer: 50 g of modified silane was added to 100 g of acrylic acid prepolymer, 0.2 g of azobisisobutyronitrile was added, heated to 120 ° C, stirred for 3 h, and an acrylic acid / silane prepolymer was obtained; S5. Preparation of zinc acrylate resin: 100 g of acrylic acid / silane prepolymer, 13 g of benzoic acid and 8.5 g of zinc oxide were stirred and mixed for 10 min, heated to 120° C., stirred and reacted for 5 h, 12 g of propylene glycol monomethyl ether was added and stirred and mixed for 0.5 h, and the reaction was terminated to obtain zinc acrylate resin.

[0025] Example 3 This embodiment provides a method for preparing zinc acrylate resin, comprising the following steps: S1. Reaction of acrylic acid and alachlor: 0.1 mol of acrylic acid and 0.095 mol of alachlor were mixed and added to 500 mL of acetonitrile, and 0.4 mol of triethylamine was added. The mixture was stirred at 65° C. for 4 h, filtered, washed, and dried to obtain an acrylic acid-alachlor complex. S2. Preparation of acrylic acid prepolymer: 3 g of 2-butyloxyethyl 2-acrylate, 4 g of acrylic acid, 1.5 g of butyl acrylate, 1 g of perfluorohexylethyl methacrylate, and 1.5 g of acrylic acid-alachlor complex were mixed, 0.07 g of azobisisobutyronitrile, 0.07 g of n-dodecyl mercaptan, and 12 g of xylene were added, heated to 115° C., and stirred for reaction for 4 h to obtain an acrylic acid prepolymer; S3. Preparation of modified silane: 1.5 g of nano-silica was added to 200 mL of ethanol, 8 g of composite silane was added, heated to 45 ° C, stirred for 1.5 h, and the solvent was removed under reduced pressure to obtain modified silane; The composite silane includes a mixture of KH570, KH550, and KH580 in a mass ratio of 3.5:2.5:1.5; S4. Preparation of acrylic acid / silane prepolymer: 40 g of modified silane was added to 100 g of acrylic acid prepolymer, 0.15 g of azobisisobutyronitrile was added, heated to 115 ° C, stirred for 2.5 h, to obtain acrylic acid / silane prepolymer; S5. Preparation of zinc acrylate resin: 100 g of acrylic acid / silane prepolymer, 12.5 g of benzoic acid and 8.2 g of zinc oxide were stirred and mixed for 10 min, heated to 115° C., stirred and reacted for 4 h, 11 g of propylene glycol monomethyl ether was added and stirred and mixed for 0.5 h, and the reaction was terminated to obtain zinc acrylate resin.

[0026] Comparative Example 1 Compared with Example 3, the difference is that no acrylic acid-alachlor complex is added in step S2.

[0027] The details are as follows: S2. Preparation of acrylic prepolymer: 3 g of 2-butoxyethyl 2-acrylate, 4 g of acrylic acid, 1.5 g of butyl acrylate, and 1 g of perfluorohexylethyl methacrylate were mixed, 0.07 g of azobisisobutyronitrile, 0.07 g of n-dodecyl mercaptan, and 12 g of xylene were added, and the mixture was heated to 115° C. and stirred for reaction for 4 h to obtain an acrylic prepolymer.

[0028] Comparative Example 2 Compared with Example 3, the difference is that 2-butoxyethyl 2-acrylate is not added in step S2.

[0029] The details are as follows: S2. Preparation of acrylic acid prepolymer: 4 g acrylic acid, 1.5 g butyl acrylate, 4 g perfluorohexylethyl methacrylate, and 1.5 g acrylic acid-alachlor complex were mixed, 0.07 g azobisisobutyronitrile, 0.07 g n-dodecyl mercaptan, and 12 g xylene were added, and the mixture was heated to 115° C. and stirred for reaction for 4 h to obtain an acrylic acid prepolymer.

[0030] Comparative Example 3 Compared with Example 3, the difference is that no perfluorohexylethyl methacrylate is added in step S2.

[0031] The details are as follows: S2. Preparation of acrylic acid prepolymer: 4 g of 2-butoxyethyl 2-acrylate, 4 g of acrylic acid, 1.5 g of butyl acrylate, and 1.5 g of acrylic acid-alachlor complex were mixed, 0.07 g of azobisisobutyronitrile, 0.07 g of n-dodecyl mercaptan, and 12 g of xylene were added, and the mixture was heated to 115° C. and stirred for reaction for 4 h to obtain an acrylic acid prepolymer.

[0032] Comparative Example 4 Compared with Example 3, the difference is that no nano-silicon dioxide is added in step S3.

[0033] The details are as follows: S3. Preparation of silane: 9.5 g of composite silane was added to 200 mL of ethanol, heated to 45 ° C, stirred for 1.5 h, and the solvent was removed under reduced pressure to obtain silane; The composite silane includes a mixture of KH570, KH550 and KH580, with a mass ratio of 3.5:2.5:1.5.

[0034] Comparative Example 5 Compared with Example 3, the difference is that steps S3 and S4 are not performed.

[0035] The details are as follows: S1. Reaction of acrylic acid and alachlor: 0.1 mol of acrylic acid and 0.095 mol of alachlor were mixed and added to 500 mL of acetonitrile, and 0.4 mol of triethylamine was added. The mixture was stirred at 65° C. for 4 h, filtered, washed, and dried to obtain an acrylic acid-alachlor complex. S2. Preparation of acrylic acid prepolymer: 3 g of 2-butyloxyethyl 2-acrylate, 4 g of acrylic acid, 1.5 g of butyl acrylate, 1 g of perfluorohexylethyl methacrylate, and 1.5 g of acrylic acid-alachlor complex were mixed, 0.07 g of azobisisobutyronitrile, 0.07 g of n-dodecyl mercaptan, and 12 g of xylene were added, heated to 115° C., and stirred for reaction for 4 h to obtain an acrylic acid prepolymer; S3. Preparation of zinc acrylate resin: 100 g of acrylic prepolymer, 12.5 g of benzoic acid and 8.2 g of zinc oxide were stirred and mixed for 10 min, heated to 115° C., stirred and reacted for 4 h, 11 g of propylene glycol monomethyl ether was added and stirred and mixed for 0.5 h, and the reaction was terminated to obtain zinc acrylate resin.

[0036] Test Example 1 The zinc acrylate resins prepared in Examples 1-3 of the present invention or Comparative Examples 1-5 were subjected to performance tests.

[0037] 1. Static contact angle: The static contact angle of water was measured using an SDC-100S contact angle meter. The resin was first dropped onto a glass slide and dried in a vacuum drying oven at 120°C for 3 hours. A coating was then formed on the glass slide and the test was performed.

[0038] 2. Static hydrolysis test: The resin is evenly coated on the surface of a glass sheet with a mass of w0 (3 parallel samples), dried to constant weight, weighed, and the mass is recorded as w1. Then the sample is placed in a glass water tank (40cm×40cm×8cm) filled with artificial seawater, soaked for 28 days, and the sample is taken out and immersed in a glass water tank filled with ultrapure water to remove surface salt stains. Then take it out and put it in a fume hood to dry for 2 hours, then put the sample in an oven at 110℃ and dry it for 2 hours, weigh it and record it as w2. The mass difference between w2 and w1 is the loss of the coating in seawater.

[0039] The results are shown in Table 1.

[0040] Table 1 Group Static contact angle (°) 28d mass loss (%) Example 1 113 14.4 Example 2 112 13.9 Example 3 115 13.2 Comparative Example 1 111 14.8 Comparative Example 2 117 16.7 Comparative Example 3 104 15.9 Comparative Example 4 107 18.2 Comparative Example 5 101 21.7 It can be seen from the above table that the zinc acrylate resins prepared in Examples 1-3 of the present invention have good hydrophobicity and a suitable hydrolysis rate.

[0041] Example 4 This embodiment provides a Wuxi self-polishing antifouling coating.

[0042] Raw material composition (parts by weight): 30 parts of zinc acrylate resin prepared in Example 1, 5 parts of rosin, 35 parts of antifouling agent, 5 parts of iron red, 5 parts of talcum powder, 0.5 parts of auxiliary agent, and 10 parts of xylene. The auxiliary agent is a mixture of wetting agent Deqian 904S, dispersant soybean lecithin, anti-settling agent Deqian 202P, leveling agent Deqian 435, and defoaming agent Dow Corning DC62, with a mass ratio of 1:1:1:1:1. The antifouling agent is a mixture of cuprous oxide, zinc dimethyl dithiocarbamate, and copper pyrithione, with a mass ratio of 1:1:1.

[0043] The preparation method comprises the following steps: Zinc acrylate resin, rosin, antifouling agent, iron red, talcum powder, additives and xylene were mixed according to the formula, stirred at 1000 r / min for 2 hours, and ground to a fineness of less than 100 μm to prepare a Wuxi self-polishing antifouling coating.

[0044] Example 5 This embodiment provides a Wuxi self-polishing antifouling coating.

[0045] Raw material composition (parts by weight): 40 parts of zinc acrylate resin prepared in Example 2, 10 parts of rosin, 45 parts of antifouling agent, 10 parts of iron red, 10 parts of talcum powder, 1 part of auxiliary agent, and 15 parts of xylene. The auxiliary agent is a mixture of wetting agent Deqian 904S, dispersant soybean lecithin, anti-settling agent Deqian 202P, leveling agent Deqian 435, and defoaming agent Dow Corning DC62, with a mass ratio of 1:1:1:1:1. The antifouling agent is a mixture of cuprous oxide, zinc dimethyl dithiocarbamate, and copper pyrithione, with a mass ratio of 1:1:1.

[0046] The preparation method comprises the following steps: Zinc acrylate resin, rosin, antifouling agent, iron red, talcum powder, additives and xylene were mixed according to the formula, stirred at 1200r / min for 4 hours, and ground to a fineness of less than 100μm to prepare a Wuxi self-polishing antifouling coating.

[0047] Example 6 This embodiment provides a Wuxi self-polishing antifouling coating.

[0048] Raw material composition (parts by weight): 35 parts of zinc acrylate resin prepared in Example 3, 7 parts of rosin, 37 parts of antifouling agent, 7 parts of iron red, 7 parts of talcum powder, 0.7 parts of auxiliary agent, and 12 parts of xylene. The auxiliary agent is a mixture of wetting agent Deqian 904S, dispersant soybean lecithin, anti-settling agent Deqian 202P, leveling agent Deqian 435, and defoaming agent Dow Corning DC62, with a mass ratio of 1:1:1:1:1. The antifouling agent is a mixture of cuprous oxide, zinc dimethyl dithiocarbamate, and copper pyrithione, with a mass ratio of 1:1:1.

[0049] The preparation method comprises the following steps: Zinc acrylate resin, rosin, antifouling agent, iron red, talcum powder, additives and xylene were mixed according to the formula, stirred at 1100r / min for 3h, and ground to a fineness of <100μm to prepare Wuxi self-polishing antifouling coating.

[0050] Comparative Example 6 Compared with Example 6, the difference is that the zinc acrylate resin is prepared from Comparative Example 1.

[0051] Comparative Example 7 Compared with Example 6, the difference is that the zinc acrylate resin is prepared from Comparative Example 2.

[0052] Comparative Example 8 Compared with Example 6, the difference is that the zinc acrylate resin is prepared from Comparative Example 3.

[0053] Comparative Example 9 Compared with Example 6, the difference is that the zinc acrylate resin is prepared from Comparative Example 4.

[0054] Comparative Example 10 Compared with Example 6, the difference is that the zinc acrylate resin is prepared from Comparative Example 5.

[0055] Test Example 2 The performance of the Wuxi self-polishing antifouling coatings prepared in Examples 4-6 and Comparative Examples 6-10 was tested. The results are shown in Table 2.

[0056] Table 2 Group Adhesion (Mpa) Impact resistance (kg·cm) Flexibility (mm) Antifouling performance (300μm) Abrasion resistance (750g / 500r) (g) <![CDATA[Copper ion leaching rate after 35d stabilization (μg / cm 2 / day)]]> Test Standards GB / T5210-2006 GB / T 1732-2020 GB / T 1731-93 GB 5370-85 GB / T 1768-2006 GB / T 6824-2008 Example 4 6.4 62 0.2 The harbor board period is 55 months 0.010 29 Example 5 6.5 60 0.3 The port board period is 54 months 0.011 30 Example 6 6.7 65 0.2 The port board period is 57 months 0.009 32 Comparative Example 6 6.1 60 0.4 The harbor board period is 36 months 0.012 28 Comparative Example 7 6.2 58 0.5 The port board period is 40 months 0.014 24 Comparative Example 8 6.0 57 0.5 The port board period is 37 months 0.013 25 Comparative Example 9 5.8 50 1.4 Seaport board period: 50 months 0.14 22 Comparative Example 10 5.6 47 2.1 The harbor board period is 48 months 0.27 20 It can be seen from the above table that the Wuxi self-polishing antifouling coatings prepared in Examples 4-6 of the present invention have good comprehensive properties.

[0057] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing zinc acrylate resin, characterized in that: The following steps are involved: S1. Reaction of acrylic acid and alachlor: acrylic acid and alachlor were mixed and added to acetonitrile, a base was added, the reaction was stirred, filtered, washed, and dried to obtain an acrylic acid-alachlor complex; S2. Preparation of acrylic prepolymer: 2-butyloxyethyl acrylate, acrylic acid, butyl acrylate, perfluorohexylethyl methacrylate, acrylic acid-alachlor complex were mixed, an initiator, n-dodecyl mercaptan and a solvent were added, and the reaction was heated and stirred to obtain an acrylic prepolymer; S3. Preparation of modified silane: adding nano-silica to ethanol, adding composite silane, heating and stirring the reaction, removing the solvent under reduced pressure to obtain modified silane; S4. Preparation of acrylic acid / silane prepolymer: adding modified silane to acrylic acid prepolymer, adding an initiator, heating and stirring the reaction to obtain acrylic acid / silane prepolymer; S5. Preparation of zinc acrylate resin: acrylic acid / silane prepolymer, benzoic acid and zinc oxide are uniformly mixed, heated and stirred to react, propylene glycol monomethyl ether is added and stirred to mix, and the reaction is terminated to obtain zinc acrylate resin.

2. The preparation method according to claim 1, characterized in that: In step S1, the molar ratio of acrylic acid, alachlor and base is 1:0.9-1:3-5, the base is selected from triethylamine, NaOH or KOH, the stirring reaction temperature is 60-70° C., and the time is 3-5 hours.

3. The preparation method according to claim 1, characterized in that: The mass ratio of 2-propenoic acid-2-butoxyethyl ester, acrylic acid, butyl acrylate, perfluorohexylethyl methacrylate, acrylic acid-alachlor complex, initiator, n-dodecyl mercaptan, and solvent in step S2 is 2-4:3-5:1-2:0.5-1.5:1-2:0.05-0.1:0.05-1:10-15, the temperature of the heating and stirring reaction is 110-120° C., the time is 3-5h, the initiator is selected from at least one of azobisisobutyronitrile, dimethyl azobisisobutyrate, azobisisovaleronitrile, and azobisisoheptonitrile, and the solvent is toluene or xylene.

4. The preparation method according to claim 1, characterized in that: The average particle size of the nano-silica in step S3 is 80-120nm, the mass ratio of the nano-silica to the composite silane is 1-2:7-10, the composite silane includes a mixture of KH570, KH550, and KH580 in a mass ratio of 3-4:2-3:1-2, the temperature of the heating and stirring reaction is 40-50°C, and the time is 1-2h.

5. The preparation method according to claim 1, characterized in that: The mass ratio of the modified silane, acrylic prepolymer and initiator in step S4 is 3-5:10:0.01-0.02, the initiator is selected from at least one of azobisisobutyronitrile, dimethyl azobisisobutyrate, azobisisovaleronitrile and azobisisoheptylonitrile, the temperature of the heating and stirring reaction is 110-120° C., and the time is 2-3 hours.

6. The preparation method according to claim 1, characterized in that: In step S5, the mass ratio of acrylic acid / silane prepolymer, benzoic acid, zinc oxide and propylene glycol monomethyl ether is 100:12-13:8-8.5:10-12, and the temperature of the heating and stirring reaction is 110-120° C. and the time is 3-5 hours.

7. A zinc acrylate resin obtained by the preparation method according to any one of claims 1 to 6.

8. A tin-free self-polishing antifouling coating containing the zinc acrylate resin as claimed in claim 7, characterized in that: 30-40 parts of the zinc acrylate resin of claim 7, 5-10 parts of rosin, 35-45 parts of antifouling agent, 5-10 parts of iron red, 5-10 parts of talcum powder, 0.5-1 parts of additives, and 10-15 parts of xylene.

9. The Wuxi self-polishing antifouling coating according to claim 8, characterized in that: The antifouling agent is at least one of cuprous oxide, zinc dimethyldithiocarbamate, copper pyrithione, and 4,5-dichloro-2-octyl-4-isothiazoline-3-one, and the auxiliary agent is at least one of a wetting agent, a dispersant, an anti-settling agent, a leveling agent, and a defoaming agent.

10. A method for preparing the Wuxi self-polishing antifouling coating as claimed in claim 8 or 9, characterized in that: The following steps are involved: Zinc acrylate resin, rosin, antifouling agent, iron red, talcum powder, additives and xylene are mixed according to the formula, stirred at 1000-1200r / min for 2-4h, and ground to a fineness of less than 100μm to prepare Wuxi self-polishing antifouling coating.

Citation Information

Patent Citations

  • Copper-free and environment-friendly self-polishing ocean antifouling paint

    CN106675294A